Hyperprogressive Disease in Malignant Carcinoma With Immune Checkpoint Inhibitor Use: A Review - Liu, Xiaojun; Qiao, Liang (Frontiers in Nutrition, 2022)
Immune checkpoint inhibitors (ICIs) have shown durable remissions and improved long-term survival across a variety of cancer types. However, there is growing evidence that a significant subset of nonresponsive patients may exhibit hyperprogressive disease (HPD) during the initiation of immune checkpoint inhibitors (ICIs). Moreover, patients with HPD triggered by ICIs are always correlated with a deteriorating quality of life and poor prognosis. The ability to predict such rapid disease progression phenotypes is of great importance. More precision parameters to evaluate the response pattern to ICIs are urgently needed. To date, the mechanisms of HPD are still unclear. Aberrant alterations of driven genes, tumor microenvironment, or T cell immunophenotype may involve in HPD. In this article, we aim to provide an updated overview of available studies on HPD and summarize the potential predictors associated with HPD and the underlying mechanisms of HPD.